(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article provides information on state regulation of investment activity, organization of the investment process, ensuring a stable environment, and the stages of production processes involving material and non-material resources among investment participants. It also discusses the essence and characteristics of investment relations.